2021
DOI: 10.1038/s41559-021-01426-y
|View full text |Cite
|
Sign up to set email alerts
|

The island rule explains consistent patterns of body size evolution in terrestrial vertebrates

Abstract: Island faunas can be characterized by gigantism in small animals and dwarfism in large animals, but the extent to which this so-called 'island rule' provides a general explanation for evolutionary trajectories on islands remains contentious. Here we use a phylogenetic metaanalysis to assess patterns and drivers of body size evolution across a global sample of paired island-mainland populations of terrestrial vertebrates. We show that 'island rule' effects are widespread in mammals, birds and reptiles, but less… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
93
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(129 citation statements)
references
References 424 publications
7
93
1
3
Order By: Relevance
“…This would explain that diurnal Socotran Pristurus have not colonized ground habitats and, therefore, their morphology has not changed substantially, while some nocturnal [29,45]. This is consistent with results on global insular vertebrate communities suggesting that the prevalence of the island rule is subjected to system-specific ecological and environmental dynamics [44]. Furthermore, a recent study on the anole radiation in the Greater Antilles did not find evidence for an island effect, pointing instead to ecological opportunity and key innovations as the drivers of the adaptive radiation [46].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This would explain that diurnal Socotran Pristurus have not colonized ground habitats and, therefore, their morphology has not changed substantially, while some nocturnal [29,45]. This is consistent with results on global insular vertebrate communities suggesting that the prevalence of the island rule is subjected to system-specific ecological and environmental dynamics [44]. Furthermore, a recent study on the anole radiation in the Greater Antilles did not find evidence for an island effect, pointing instead to ecological opportunity and key innovations as the drivers of the adaptive radiation [46].…”
Section: Discussionsupporting
confidence: 88%
“…Our results reveal a complex scenario in which different morphological traits interact with ecological characteristics of the species in different ways, suggesting a differential relevance of body size and shape proportions for the adaptation to specific habitats. The tendency of island taxa to diverge in morphology compared to their continental relatives is a general pattern in terrestrial vertebrates, especially concerning body size [43,44]. In fact, recent studies on Afro-Arabian geckos colonizing the Socotra Archipelago found support for this island effect, particularly in the genus Hemidactylus [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Tethyshadros and its assemblage from VdP with its unique chronostratigraphic setting would represent the evidence of one of these dispersal events, where at least the northern margin of the proto-Italian microplate assemblages hosted a diverse fauna of Asian origins. With the new evidence provided herein, we confute the presence of the co-set of geographic and environmental constraints necessary to trigger evolutionary modes towards insular dwarfism 2 , 87 , analogous to those reconstructed for the Maastrichtian Hațeg domain. The earlier dating coincided with a time of less extensive fragmentation of this region, and the higher connectivity with the wider, continental Asian domain is indicative of potentially higher biotic interchange, if not vicariance with the Asian biogeographic province.…”
Section: Discussionsupporting
confidence: 60%
“…Crouch & Tobias, 2022) and geographical context (e.g. Benítez-López et al, 2021) in driving phenotypic evolution. With the rapid ongoing improvement of avian phylogenies and the associated toolkit of evolutionary models, AVONET trait data offer an unparalleled template for future analyses of this kind.…”
Section: Ac Roevolu T Ion a N D Genom Ic Smentioning
confidence: 99%
“…The availability of AVONET trait data allows variation in morphological traits to be mapped and analysed at global scales with reduced sampling bias. The first phase of such analyses included tests of geographical gradients in dispersal-related traits (Sheard et al, 2020) and the role of island colonisation as a driver of predictable trajectories of trait evolution-the so-called 'island rule' (Benítez-López et al, 2021). Further studies are needed to explore numerous other putative ecogeographical patterns, such as Bergmann's and Allen's rules, in greater detail.…”
Section: Ac Roecology a N D Com M U N I T Y Ecologymentioning
confidence: 99%